Administrative Burden Borne by the Department of Cooperatives, Micro Enterprises, Industry and Trade of Semarang Regency - Husaini, Wahyu Nurul; Mohammad Arifin (Arkus, 2024)
Humans have a central role in the overall dynamics of the organization, especially in the context of the Department of Cooperatives, Micro Enterprises, Industry, and Trade (Disperindag) of Semarang Regency. The role of humans as organizers and managers of organizational activities is the key to success, with competent human resources (HR) being assets that must continue to be trained and developed. The success of an organization really depends on the ability of human resources to achieve the goals that have been set. However, HR is also faced with challenges, both internal and external. Internal factors include an individual's personal abilities, while external factors involve changes in policies and regulations, which can affect employee performance. Technological limitations, especially among senior employees, are an obstacle to achieving optimal performance, requiring additional efforts to adapt to current developments. The Semarang Regency Department of Industry and Trade, as a government agency, is facing various problems, especially regarding employee workload in dealing with changes in regulations and internet-based work systems. These obstacles can affect employee performance, requiring further adjustment and training efforts. Therefore, understanding and handling these factors is the key to increasing effectiveness and efficiency in achieving organizational goals.